KALIMANTAN DALAM WACANA INDIANISASI - Hindarto, Imam (Naditira Widya, 2008)
Trade that began to flourish during the early phase of the Anno Dominion generated the growth of lndicinfluenced- region in Southeast Asia. Such influence is widely evident in the Indonesian Archipelago including Kalimantan, which is practically located in the middle of ancient trading streams. lndic influenced archaeological remains are abundantly discovered in Kalimantan, for instance statues and inscriptions. Foreign and Indonesian scholars have long discussed and present hypotheses on the possible agent of the 'indianiazing' of the Indonesian Archipelago. In regard to obtain a thorough understanding on the Indonesian historical-cultural discourse, this article discusses the importance of re-evaluating those hypotheses.